Psychological Capital and Employee Job Performance: The Mediating Role of Burnout in the Banking Sector - Chaudhary, Manoj Kumar; Dhungana, Madan; Adhikari, Juhi (Journal of Emerging Management Studies, 2024)
Purpose – With an emphasis on the mediating function of occupational burnout in Nepal’s banking industry, the paper investigates the relationship between psychological capital (PsyCap) and employee job performance. Design/methodology/approach – The research utilized convenience sampling technique to gather data from 318 respondents within a descriptive and causal research framework. Based on the Job Demands-Resources (JD-R) theory, the research employed a five-point Likert scale to measure the variables. Hypotheses were tested using regression modeling and correlation analysis. Additionally, the bootstrap resampling technique was implemented with Hayes’ PROCESS macro for mediation analysis in SPSS. Findings and conclusion – The research discovered a positive relationship between psychological capital (PsyCap) and job performance, indicating that employees with higher PsyCap typically perform better. Additionally, the results indicated that burnout is a partial mediator in this relationship, indicating that PsyCap directly and indirectly improves job performance by mitigating occupational burnout. Implication – The research is valuable for organizations and policymakers aiming to create healthier and more productive workplaces. It enables leaders and managers to comprehend how psychological traits such as optimism, resilience, self-efficacy, and hope can improve work output and lessen burnout. The study also highlights the importance of managing stress to benefit fully from employees’ psychological strengths. Originality/value – With burnout as a mediating factor, the research is one of the few to examine the association between psychological capital (PsyCap) and work performance in the banking sector. As such, it significantly advances Nepalese literature in this area. It tackles largely unexplored topic in the banking sector and thoroughly examines the PsyCap’s four dimensions – hope, self-efficacy, resilience, and optimism and their effects on job performance and burnout.